Relatório de Estágio Profissional "Por mais longa que seja a caminhada o mais importante é dar o primeiro passo" - Ana Elisa Bessa Menezes Araújo Paiva (2019)
The Professional Internship is inserted in the study plan of the second year of the Master's Degree in Teaching in Physical Education in Primary and Secondary Education, from FADEUP. It presents itself as the last step of initial training, and it's where the intern is confronted with the real world for the first time. It's within this confrontation that all the academic knowledge acquired throughout the initial training is going to be put into practice. The Internship Report mirrors the path of an intern by presenting different learnings and experiences lived at a school in the district of Barcelos. This document is structured in five chapters: the first chapter is the introduction. The second is related to the personal dimention where I talk about my life experience and what has influenced me to choose this profession. The third, the institutional framework, I mention the role of the intern and the importance of Physical Education in students' lives. I portrait the Professional Internship on a legal and institutional level, I present the cooperating school as well as my classes, keeping in mind the role of the intern, the cooperating professor, the thesis advisor and the meaning of the internship group. The fourth chapter, the execution of the professional internship, is organised around three major areas: area 1 - organisation and management of teaching and learning which highlights themes such as conception, planning, performance, observation and evaluation; area 2 - participation in the school and relationship with community which incorporates all the activities performed by the intern for the educational community; area 3 - professional development which includes the investigation study "Does the model of Sports Education influences students' motivation?". Finally, the fifth chapter where I give my final balance of this year emphasising what was for me being a teacher and the importance of this experience in my professional life as well as my expectations for the future.